The Future of Astrometry in Space - Vallenari, Antonella (Frontiers in Astronomy and Space Sciences, 2018)
This contribution focuses on the importance of astrometry and on its future developments. Over the centuries astrometry has greatly contributed to the advance of the knowledge of the Universe. Nowadays a major breakthrough is on the way due to astrometric sky surveys from space. ESA space missions Hipparcos first and then Gaia point out the outstanding contribution that space astrometry can provide to our knowledge in many fields of astrophysics, going from the Milky Way formation and evolution, to stellar astrophysics, extra-galactic astrophysics, and fundamental physics. We briefly outline the properties of Gaia first and second data release, and the accuracies expected end-of-mission. The next big advance in space astrometry would be either to improve the astrometric accuracy of one order of magnitude, or to move to a different wavelength domain. While both options have the potential to bring us in a new era of discovery, they have to face enormous issues. We summarize the future directions in space astrometry that are proposed or under investigation by the scientific community, their main challenges and the expected outcome.